Exploring the Perceived Effects of Principal Leadership Style on Teachers’ Job Performance in Afghanistan - Maroof, Aminullah (ADA University, 2023)
This study aims to explore the effects of principal’s leadership styles on teachers' job performance in private schools in Kabul, Afghanistan through teachers', principals', and head of department perceptions. This study was guided by the following two research questions: I. What are the leadership styles being employed by principals in private schools in Afghanistan? II. How do those styles influence teachers’ job performance in private schools in Afghanistan? The explorative qualitative research design was adopted to study principals’ leadership style's influence on teachers' job performance in private schools in Kabul. The study was conducted in three private schools in Kabul, which were chosen by utilizing convenience sampling of the non-probability sampling method. Accordingly, a one-on-one online interview instrument was used to collect data from six teachers, three principals, and one HoD (head of department). The findings of this study suggest that principals in private schools in Kabul utilize transformational, transactional, and instructional leadership styles, but transactional leadership style is widely employed by principals in Afghanistan. Furthermore, the findings the indicate that transformational and instructional leadership styles positively influence teachers' job performance; however, transactional leadership employed by principals has a negative effect on teachers' job performance.
Keywords: Educational leadership--Afghanistan; Leadership styles--Private schools--Afghanistan; Teachers--Job performance--Afghanistan; Transformational leadership--Education--Afghanistan; School management--Afghanistan; Afghanistan--Educational policy; Education